Cropping geometry and nutrient management study on winter maize (Zea mays) + potato (Solanum tuberosum) intercropping - VERMA, V K; MEENA, R N; SINGH, D N; UPADHYAY, P K; SINGH, RAJESH KUMAR; SINGH, RAJIV KUMAR (The Indian Journal of Agricultural Sciences, 2021)
Field experiment was conducted during rabi during 2015-16 and 2016-17 at Varanasi (UP) to study the effect of cropping geometry and nutrient management on winter maize (Zea mays L.) + potato (Solanum tuberosum L.) intercropping. Among the crop geometry, winter maize intercropped with potato (1:1) in replacement series showed significantly higher growth parameters of maize, viz. dry matter accumulation, crop growth rate and number of green leaves per plant as compared to additive series but it was found at par when winter maize grown with potato (1:2) in replacement series. However, growth parameters of potato differed interchangeably as compared to maize in winter maize + potato intercropping system during both the years. Significantly higher grain yield of winter maize and potato were found in intercropping with 1:1 and 1:2 in additive series, respectively. Assessment of intercropping indices and economics of maize and potato proved to be better in additive series as compared to replacement series during both the years of experimentation. Amongst nutrient management, growth parameters, yield attributes and yield, intercropping indices and economics of winter maize + potato were recorded significantly higher with the application of 100% RDF + 25% N through poultry manure followed by the application of 100% RDF + 25% N through vermicompost as compared to rest of the treatments during both the years. Thus, it may be concluded that the maize + potato intercropping in additive series with integration of poultry manure as N source gives better yield and economics of both the crops.